PENGARUH UKURAN PERUSAHAAN, RISIKO BISNIS, GROWTH,PROFITABILITAS, LIKUIDITAS, DAN SALES GROWTH TERHADAP STRUKTUR MODAL PADA SEKTOR FARMASI YANG TERDAFTAR DI BEI - ROBERT KALIMAN; SATRIYO WIBOWO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to test and analyze empirically the influence of firm size, business risk, growth, profitability, liquidity and sales growth toward capital structure.The object of this research is company in pharmacy industry that listed in Indonesia Stock Exchange period 2010-2015. The purposive sampling is used as sampling technique, where 9 companies met the criteria and were analyzed using Eviews 8 panel data regressions with fixed effect model to test the hypothesis.The result of this research shows that firm size, profitability and liquidity influence capital structure, while business risk, growth, dan sales growth do not influence capital structure.